EUR/USD Q4 2021 TECHNICAL OUTLOOK - Manunggal, Bagus (International Journal of Business, Law, and Education, 2020)
During the months of July to August, reports on the US economy were not very good. Many of the results did not match the expectations of economists. On the other hand, EUR exceeded expectations, but the trend is likely to decline. Meanwhile, in 2021, only Q4 remains. This study attempts to describe the opportunities in Q4 2021 and how to optimize profits on EUR/USD trading. Overall, EUR/USD tends to be bearish. However, with the unfavorable report on the US economy, the upward trend was quite significant throughout July-August. So there is a short sell opportunity, but by first testing the 1.1900 level. If the price is able to break through this level, EUR/USD will continue to be bullish. However, if the price is unable to penetrate that level, the price will have a bearish opportunity according to the major trend.